Polymorphism of the IGF2 gene, birth weight and grip strength in adult men. - Sayer, A; Syddall, H; O'Dell, S; Chen, X; Briggs, P; Briggs, R; Day, I; Cooper, C (2002)
BACKGROUND: Grip strength is a simple measure of skeletal muscle function but a powerful predictor of disability, morbidity and mortality. Recent evidence has shown that prenatal and infant growth influence grip strength in later life; this may reflect genetic influences on muscle size and function, although strong candidate genes have not been identified. IGF II has proliferative effects in adult muscle and is one of the major determinants of fetal growth; polymorphism in the IGF2 gene could therefore link early growth to adult grip strength. OBJECTIVES: To determine whether polymorphism of the IGF2 gene influences adult grip strength and mediates the association between size at birth and grip strength in later life. METHODS: Polymorphism of the ApaI marker in the IGF2 gene was determined for 693 Hertfordshire men and women born between 1920 and 1930 who had taken part in a study linking early growth to ageing. Grip strength was measured using isometric dynamometry. Genotyping assay development was undertaken in Southampton Genetic Epidemiology Laboratories (http://www.sgel.humgen.soton.ac.uk). RESULTS: In univariate analyses, IGF2 genotype and birth weight were both significant predictors of adult grip strength in the men after adjustment for age and current height. Significant associations were not seen in the women. When IGF2 genotype and birth weight in men were studied simultaneously, both contributed significantly to grip strength after adjustment for age and adult height. CONCLUSIONS: These results show that polymorphism of the IGF2 gene and birth weight have independent effects on adult grip strength in men and suggest that IGF2 polymorphism does not explain the association between size at birth and grip in later life. This study provides preliminary evidence for independent genetic and early environmental programming of adult muscle strength.